(untitled) (Diametros, 2019)
The phenomenal body is an intriguing concept, and Merleau-Ponty’s notion of habit, coupled with motor intentionality, provides a novel perspective on its inner workings. I contend that his portrayal of habit tacitly bears two faces – motoric habit and instrumental habit respectively. The former is an attunement to some bodily possibilities that are already at our disposal while the latter is an explicit relation to external objects and a process of incorporating those objects into our own bodies. These two notions play into each other, creating a mechanism that offers an intuitive illustration and simple productive definition for a dynamic picture of bodyhood. Furthermore, it carries an internal delimitation that marks the boundaries of its application. The result is a view that provides something new to current interpretations of Merleau-Ponty, as well as potential applications in areas that derived from his appeals to motor intentionality.